Anti-Inflammatory Effect of Anthill Ointment Extract (Myrmecodia pendens) on White Rats - Indah Amelia Rizky; Fajar Maulana; Heti Aisyah; Anggraini Palino; Miftahul Jannah; Angga Bayu Budiyanto (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Inflammation is the body's response to foreign substances that enter the body and is characterized by redness, fever, swelling, pain, and impaired organ function. Anti-inflammatory is a term for substances or medicines that work to reduce or suppress the inflammatory process. One of the plants originating from Papua is anthill (Myrmecodia pendens). Ant nest (Myrmecodia pendens) contains lots of synthetic secondary metabolite substances such as flavonoids, saponins, tannins, and alkaloids. That ingredient is presumed to have an effect as anti-inflammatory. This research aims to examine the anti-inflammatory effectiveness of anthill ointment extract (Myrmecodia pendens) on the feet of white rats induced by carrageenan. The test group was divided into 5 groups in which each group consisted of 3 rats. The positive control group was subjected to bioplacenton, the negative control to ointment base, and the extract group to anthill ointment extract (Myrmecodia pendens) with concentrations of F1 (10%), F2 (20%), and F3 (40%). The test was conducted by inserting 1% carrageenan liquid into the sole of the rat's right paw. The volume of edema was measured using a syrup bottle filled with water every 60 minutes for 360 minutes. The data were analyzed statistically using (ANOVA) and obtained data p = 0.580 > 0.05. The conclusion of this research is that there is no significant difference in the percent of anti-inflammatory power between the dose groups F1 (10%), F2 (20%) and F3 (40%) with positive control.